Analisa Faktor yang Berhubungan dengan Status Gizi Ibu Hamil pada Masa Pandemi Covid-19 di Puskesmas Portibi Kabupaten Padang Lawas Utara - Sahari Bulan Harahap; Asriwati Asriwati; Mappeaty Nyorong (PubHealth Jurnal Kesehatan Masyarakat, 2022)
Lack of or excess nutrition during pregnancy during the COVID-19 pandemi can have an adverse effect on the health of the mother and fetus. The fulfillment of the nutritional adequacy of pregnant women in the working area of ​​the Portibi Health Center is still relatively low. The purpose of this studywas to analyze factors related to the nutritional status of pregnant women during the COVID-19 pandemi in the working area of ​​the Portibi Health Center. The type of research used in this research was an analytic survey with a cross sectional study design. The study was conducted in the Work Area in the work area of ​​the Portibi Health Center in 2021. The sampling technique in this study was a total sampling of 48 people. To analyze the data is to use logistic regression test. Based on the results of univariate research, it is known that of the 48 pregnant women studied, most of the pregnant women aged 36-45 years, namely 21 (43.75%), high school education, as many as 25 (52.08%) people, working as farmers as many as 24 (50.00%) pregnant women. Bivariate results showed that there was a relationship between knowledge and nutritional status of pregnant women (p = 0.002), there was a relationship of trust with the nutritional status of pregnant women (p = 0.024), there was a relationship between socioeconomic status and nutritional status of pregnant women (p = 0.006), there was a relationship between access to transportation with nutritional status of pregnant women (p = 0.030). It was recommended that pregnant women buy affordable foodstuffs, because nutritious food does not have to be expensive. For example carrots, sea fish, tomatoes and others and make food stocks at home for a few days if the house is far from the market.